Analysis of the F1 and F2 generations of experimental and commercial hybrid sorghum - Hernández Espinal Luis Alberto; Moreno Gallegos Tomás (Revista Mexicana de Ciencias Agrícolas, 2018)
The price of the F1 hybrid seed of sorghum [Sorghum bicolor (L.) Moench.] is expensive, rainfed producers mainly sow seed advanced or F2 generation. The aim of this study was to evaluate the yield of grain sorghum F2 generation, compared to F1. We estimated the cost-benefit ratio (B/C) of 20 experimental and 14 commercial hybrid sorghum under irrigated conditions in the CEVACU, Culiacán, Sinaloa, Mexico. From 2010- 2012, two experiments were established with a complete block design with three replications. The average grain yield was reduced 50.79% in F2 with respect to F1. The highest grain yield in F1 hybrid obtained in experimental SHS- 23 x 43 (7 109 kg ha-1) and commercial hybrid G STAR 7304 (6813 kg ha-1). The B/C average F2 generation was lower with 45.61% with respect to F1. The results indicate that the use of advanced generation seed or F2 is not recommended because on average over 90% sorghum hybrids the B/C is negative, being uneconomical for the production of grain.